Pulse Wave Velocity Assessment for Cardiovascular Risk Prognostication in ESKD: Weighting Recent Evidence - Georgianos, Panagiotis I.; Vaios, Vasilios; Eleftheriadis, Theodoros; Zebekakis, Pantelis E.; Liakopoulos, Vassilios (Current Vascular Pharmacology, 2021)
Background: Among patients with end-stage kidney disease (ESKD), arterial stiffness is considered as a powerful predictor of cardiovascular (CV) morbidity and mortality. However, the relevance of aortic pulse wave velocity (PWV) as a prognostic biomarker for CV risk estimation is not yet fully clear. Methods: We performed a systematic search of Medline/PubMed database from inception through August 21, 2019 to identify observational cohort studies conducted in ESKD patients and exploring the association of PWV with CV events and mortality. Results: Whereas “historical” cohort studies showed aortic PWV to be associated with higher risk of CV and all-cause mortality, recent studies failed to reproduce the independent predictive value of aortic PWV in older ESKD patients. Studies using state-of-the-art prognostic tests showed that the addition of aortic PWV to standard clinical risk scores could only modestly improve CV risk reclassification. Studies associating improvement in PWV in response to blood pressure (BP)-lowering with improvement in survival cannot demonstrate direct cause-and-effect associations due to their observational design and absence of accurate methodology to assess the BP burden. Conclusion: Despite the strong pathophysiological relevance of arterial stiffness as a mediator of CV disease in ESKD, the assessment of aortic PWV for CV risk stratification in this population appears to be of limited value. Whether aortic PWV assessment is valuable in guiding CV risk factor management and whether such a therapeutic approach is translated into improvement in clinical outcomes, is an issue of clinical relevance that warrants investigation in properly-designed randomized trials.
Keywords: prognosis